2012
DOI: 10.1186/1471-2431-12-179
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and atopy in children born by caesarean section: effect modification by family history of allergies – a population based cross-sectional study

Abstract: BackgroundStudies on the association of birth by caesarean section (C/S) and allergies have produced conflicting findings. Furthermore, evidence on whether this association may differ in those at risk of atopy is limited. This study aims to investigate the association of mode of delivery with asthma and atopic sensitization and the extent to which any effect is modified by family history of allergies.MethodsAsthma outcomes were assessed cross-sectionally in 2216 children at age 8 on the basis of parents’ respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 36 publications
2
52
1
2
Order By: Relevance
“…Our goal was to test whether children born by cesarean delivery were more likely to have poor physical and socioemotional outcomes compared with children born vaginally. In line with previous research findings, 10,[12][13][14] we hypothesized that children born by cesarean delivery are more likely to experience asthma and allergies in their early years of life and have a higher BMI compared with their vaginally delivered peers.…”
Section: What This Study Addssupporting
confidence: 70%
See 1 more Smart Citation
“…Our goal was to test whether children born by cesarean delivery were more likely to have poor physical and socioemotional outcomes compared with children born vaginally. In line with previous research findings, 10,[12][13][14] we hypothesized that children born by cesarean delivery are more likely to experience asthma and allergies in their early years of life and have a higher BMI compared with their vaginally delivered peers.…”
Section: What This Study Addssupporting
confidence: 70%
“…[3][4][5][6] For example, studies have reported that children born by cesarean delivery may have increased rates of respiratory illness in their first year of life 5,7,8 and beyond, 9,10 and relationships have also been described with diabetes 11 and child overweight and obesity. 12,13 Notwithstanding these potential adverse associations, children born by cesarean delivery are usually healthy, and it is important to recognize that many factors influence child health other than mode of birth.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The German MAS-90 study reported decreased sensitization rates in vaccinated children [25], while in our cohort the few individuals ( n = 24) who were not vaccinated also demonstrated a sensitization rate >50%. Earlier studies, including higher numbers of participants born by cesarean, showed a significantly increased risk for atopy for this delivery mode [26]. A protective effect of breastfeeding on the development of allergic diseases has been suggested [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Infants born by CS have a higher incidence of respiratory distress 38 and appear to be at higher risk for developing asthma and atopy 39 , obesity 40 and type 1 diabetes 41 . It has been hypothesized that delayed and aberrant intestinal colonization might contribute to this risk conferred by CS.…”
Section: West 11mentioning
confidence: 99%